Zearalenone adsorption capacity of lactic acid bacteria isolated from pigs - Vega, María F. (2017)
The ability to adsorb zearalenone by five strain of lactic acid bacteria was evaluated: four strains of Lactobacillus spp. isolated from pig rectal swabs and one commercial strain (Lactobacillus rhamnosus). Several factors affecting the adsorption capacity were evaluated in order to improve the adsorption of the mycotoxin by bacteria. The stability of the zearalenone–bacteria complex was analyzed. In every case, bacterial adsorption capacity was higher than 40.0%. The strain showing the highest adsorption (68.2%) was selected for the following steps of this research. The adsorption percentages obtained after processing 6.5 and 7.5 mL MRS broth were 57.40% + 3.53 and 64.46% + 0.76, respectively. The stability of zearalenone–bacteria complex was evaluated by successively rinsing. In the first rinsing step 42.26% + 0.414 was still bound. In the second rinsing step 25.12% + 0.664 was still bound, whereas 15.82% + 0.675 remained in the pellet after the third rinse. Results obtained demonstrated that Lactic Acid Bacteria has capacity to adsorb zearalenone. Finally adsorption was increased using a higher volume of initial broth. These results could be used to design a new lyophilized powder for detoxification, using lactic acid bacteria as potential zearalenone adsorbents.